Effect of kickboxing training on total sulfhydryl (–SH) and ischemia-modified albumin (IMA) levels: a comparative study between athletes and sedentary individuals - Ağlar, Sinan; Karabağ, Sefer; Güler, Mehmet Şirin; Akbay, Halil İbrahim; Yasin, Amani Tahsin; Demir, Canan; DEMİR, Halit (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to investigate the impact of kickboxing training on oxidative stress biomarkers, specifically total sulfhydryl (–SH) and ischemia-modified albumin (IMA) levels. The study was designed as a quantitative, cross-sectional, comparative investigation. The sample consisted of 45 healthy male university students aged 18–24 years from the Van province, Türkiye. Participants were divided into two groups: kickboxing athletes and sedentary controls. The experimental group (n = 20) consisted of male kickboxing athletes with a minimum of seven years of training experience, ranked among the top three in the Turkish Kickboxing Championship, and currently training at least four days per week. The control group (n = 25) consisted of sedentary male individuals with no history of regular exercise in the past six months, no alcohol or tobacco use, no chronic diseases, and adherence to a balanced diet. Blood samples were analyzed using validated biochemical methods. The results showed significantly higher –SH and lower IMA levels in the kickboxing group (p < 0.05). Effect size analysis indicated large differences for both markers (Cohen’s d = 1.25 for –SH and d = 1.00 for IMA), suggesting that kickboxing training has a substantial impact on oxidative stress parameters. These findings highlight the physiological benefits of regular high-intensity physical activity in promoting cellular resilience and adaptive responses.